2009
DOI: 10.4049/jimmunol.0803548
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Human Antigen-Specific CD4+ T Cells in Peripheral Blood Revealed by Stimulated Coexpression of CD25 and CD134 (OX40)

Abstract: Ag-specific human CD4+ memory T lymphocytes have mostly been studied using assays of proliferation in vitro. Intracellular cytokine and ELISPOT assays quantify effector cell populations but barely detect responses to certain recall Ags that elicit strong proliferative responses, e.g., tetanus toxoid, that comprise non-Th1 CD4+ cells. We have found that culturing whole blood with Ag for 40–48 h induces specific CD4+ T cells to simultaneously express CD25 and CD134. This new technique readily detects responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
212
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 160 publications
(225 citation statements)
references
References 33 publications
13
212
0
Order By: Relevance
“…1). This result, plus our previously published data [19], confirmed that CD4 + CD25 + CD134 + T cells identified after a 44 hours Ag stimulation, and the CD39 + and CD39 − populations therein, up-regulate the activation markers CD25 and CD134 due to TCR stimulation, not through bystander activation.Regardless of Ag stimulus, we consistently observed that a substantial proportion of Ag-specific CD4 + CD25 + CD134 + T cells responding to stimulation expressed CD39 (30-60%), with the magnitude varying by Ag and individual (Fig. 1A).…”
supporting
confidence: 79%
See 4 more Smart Citations
“…1). This result, plus our previously published data [19], confirmed that CD4 + CD25 + CD134 + T cells identified after a 44 hours Ag stimulation, and the CD39 + and CD39 − populations therein, up-regulate the activation markers CD25 and CD134 due to TCR stimulation, not through bystander activation.Regardless of Ag stimulus, we consistently observed that a substantial proportion of Ag-specific CD4 + CD25 + CD134 + T cells responding to stimulation expressed CD39 (30-60%), with the magnitude varying by Ag and individual (Fig. 1A).…”
supporting
confidence: 79%
“…In order to test whether CD39 staining would reveal a FOXP3 + sub-population of memory CD4 + T cells, we utilised our previously described 44 hours activation assay that identifies CD4 + T-cell Ag recall responses through the induced co-expression of CD25 and CD134 [19]. We incubated healthy donor whole blood with staphylococcus enterotoxin B (SEB), PHA, tetanus toxoid (Tet Tox), CMV lysate and HSV for 44 hours and then stained with anti-CD3, -CD4, -CD25, -CD134, -CD39 and -FOXP3 mAbs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations